PENGEMBANGAN ADOBE FLASH PROFESSIONAL CS6 YANG BERORIENTASI PADA PEMAHAMAN KONSEP MATEMATIK PESERTA DIDIK - Linda Herawati; edi hidayat; depi setialesmana (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2022)
Interactive multimedia works as an interactive media in learning. The aim of this research is to develop and determine the feasibility. The method used in this research is Research Development with quantitative research methods. This research creates an interactive multimedia assisted by Adobe Flash Professional CS6 that is geared towards understanding mathematical concepts then by whole material experts, mathematical concept comprehension experts, learning design experts and multimedia experts, the feasibility of the product under construction, until the final design is obtained in the form of an interactive model multimedia product developed on the basis of the ADDIE development model. Data analysis with ADDIE. The results of this research are interactive multimedia assisted by Adobe Flash Professional CS6, the development of interactive multimedia geared towards the understanding of mathematical concepts of students using the ADDIE development process which includes analysis, design, development, implementation implementation and evaluation. The design shows that the navigation structure did not work on all elements of interactive multimedia, the display is not yet colorful and eye-catching, the content of the presented material conforms to the user's specifications, the sound effects are complete. The feasibility of interactive multimedia geared towards understanding students' mathematical concepts by experts on the entire material, experts in understanding mathematical concepts, experts in learning design and multimedia experts on content validity and validity construction shows that the product is usable. The final interactive multimedia design is the result of the media feasibility test and the first review phase. The final interactive multimedia design is the result of the media feasibility test and the first review phase. The final design shows that the product is easy to use as it is configured with a simple navigation system, colorful and eye-catching screen, games and sound effects that make learning math more interesting and memorable. Face validity responses show that clarity of text, images, audio and animation gets a very understandable category, clarity of language gets a very understandable category, ease of use of multimedia gets a very understandable category and the ease of learning of the material gets an understandable category. Overall, the response from the students was very good and resulted in an interactive multimedia final product geared towards understanding mathematical concepts.